PERAN PERUSAHAAN SAWIT PT.KALIMANTAN BINA PERMAI DALAM MENINGKATKAN EKONOMI MASYARAKAT DI KECAMATAN BELITANG HULU KABUPATEN SEKADAU - Darmansah, Darmansah (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
The existence of a company in an area in Indonesia is expected to have a positive impact on the local community, both in the form of developments in the community's economic and social and cultural sectors. The impact on the economic sector is expected that the existence of a company can increase community income, provide jobs and help improve the infrastructure around the company's operations. With the existence of the oil palm plantation company PT Kalimantan Bina Permai has provided a very positive role for the community in the company's operational area, especially in the aspect of various infrastructures, both in the form of improving access to community transportation and creating new infrastructure needed by the local community outside of company assistance in the Health sector and the Education sector. In addition, the company also helps the community in improving economic status in the form of providing and absorbing labor for the community in the company's operational area and playing a role in increasing community income which was much better before.